Memory in Motion. Archives, Technology, and the Social - Lundemo, Trond; Røssaak, Eivind; Blom, Ina (Recursions, 2016)
How do new media affect the question of social memory? Social memory is usually described as enacted through ritual, language, art, architecture, and institutions ? phenomena whose persistence over time and capacity for a shared storage of the past was set in contrast to fleeting individual memory. But the question of how social memory should be understood in an age of digital computing, instant updating, and interconnection in real time, is very much up in the air. The essays in this collection discuss the new technologies of memory from a variety of perspectives that explicitly investigate their impact on the very concept of the social. Contributors: David Berry, Ina Blom, Wolfgang Ernst, Matthew Fuller, Andrew Goffey, Liv Hausken, Yuk Hui, Trond Lundemo, Adrian Mackenzie, Sónia Matos, Richard Mills, Jussi Parikka, Eivind Røssaak, Stuart Sharples, Tiziana Terranova, Pasi Väliaho.